Prehranska revščina med skupnostjo in korporacijami - Zidar, Romana (Socialno delo, 2015)
Discourses about food and poverty are being created that directly influence our understanding of causes, consequences and ways of solving the problem of poverty. The article deals with two issues relevant for social work: the discourse about what to do with food surplus, and the discourse about food self-sufficiency in relation to our attitude towards the poor (the unemployed, precarious workers, the retired, the employed poor etc.). It is shown that instruments of public social policies are being replaced by food surplus distribution through the ecology rhetoric. This hides inequalities, encourages invasion of business practices on the field of social security, and divides people on the basis of consuming practices to consumers and non-consumers. The authors show that those who are more well-off can much easier affort to be food self-sufficient. Food production via gardening doesn't have very pronounced economic benefits (compared with buying cheap food in supermarkets), but has an important social, collective aspects. Gardening can also be understood as an ideological space where like-minded people meet. This can have some negative sides as well, as community gardens can become places with no physical borders, but with visible systems of exclusion and control.
Keywords: food; samooskrba; self-sufficiency; presežki; hrana; surplus; income; dohodek; consumerism; potrošništvo; community social work; skupnostno socialno delo